DEVELOPMENT OF A THREE DIMENSIONAL GEOMETRIC THINKING TEST FOR EARLY GRADERS - Denizli, Zeynep Akkurt; Erdogan, Abdulkadir (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2018)
This study aimed to develop a three-dimensional geometric thinking test to determine the geometric thinking of early graders in the paper-pencil environment. First, we determined the components of three-dimensional geometric thinking and prepared questions for each component. Then, we conducted the pilot studies of the test at three stages in six state schools located in the city of Ankara in Turkey. The first draft test consisting of 54 items was administered to 384 students; the second draft test consisting of 53 items was administered to 120 students and the third draft test consisting of 45 items was administered to 268 students. In order to establish the content validity of the test, prior to all the administrations, it was subsumed to the review of 13 experts and by considering the content validity rates, the items to be included in the test were determined. As the items in the test are scored as correct/false (1/0), KR-20 reliability coefficient was used in the calculation of the reliability of the test. In the last administration, KR-20 reliability coefficient was found to be 0.87; thus, it was concluded that the test is reliable.